Vitamin D levels and antenatal complications in pregnant Nigerian Igbo women - Joseph Ifeanyi Brian-D Adinma; Joseph Eberendu Ahaneku; Echendu Dolly Adinma; Joseph Odilichukwu Ugboaja; Victor Nwabunwanne Oguaka; Nneoma Dolores Adinma-Obiajulu; Mark Matthew Edet (Journal of Applied Sciences and Clinical Practice, 2022)
Background: Serum levels of Vitamin D have been linked to some complications in pregnancy such as diabetes mellitus and premature rupture of membranes (PROM). While some studies suggest inverse relationship between serum Vitamin D levels and poor pregnancy outcomes, others report a J-shaped (curvilinear) or U-shaped relationship. Objective: The objective of the study is to determine the relationship between serum Vitamin D and some selected pregnancy complications among pregnant Nigerian Igbo women. Subjects and Methods: A prospective, cross-sectional study conducted on 256 consecutive consenting antenatal women in Anambra state, Southeastern Nigeria. Maternal blood obtained was assayed for 25 hydroxyvitamin D3 using high-pressure liquid chromatography. A pro forma was used to elicit information with respect to the biosocial characteristics of the subjects. Data obtained were analyzed using SPSS version 23, and the relationship between Vitamin D levels and antenatal complications was determined using Chi-square at P < 0.05 at 95% confidence interval being considered statistically significant. Results: The overall results showed that no participant had hypovitaminosis D. It also showed that there is maximum safe limit for serum Vitamin D beyond which the prevalence of hypertensive disorders/preeclampsia, preterm labor, and PROM rises. However, higher serum Vitamin D appears to be protective against clinical and laboratory-diagnosed malaria and malaria parasitemia. The study showed an inverse relationship between the degree of malaria parasitemia and serum Vitamin D levels. Conclusion: Despite the importance of Vitamin D in both skeletal and extra-skeletal health, there appears to be a safe upper limit. Therefore, Vitamin D supplementation should be reserved for proven cases of hypovitaminosis in pregnancy, especially in our locality where there is abundance of sunshine and low prevalence of hypovitaminosis D.